2011
DOI: 10.1124/mol.111.073502
|View full text |Cite
|
Sign up to set email alerts
|

Nectandrin B Activates Endothelial Nitric-Oxide Synthase Phosphorylation in Endothelial Cells: Role of the AMP-Activated Protein Kinase/Estrogen Receptor α/Phosphatidylinositol 3-kinase/Akt Pathway

Abstract: We revealed previously that nectandrin B isolated from Myristica fragrans (nutmeg, Myristicaceae) functions as a potent AMP-activated protein kinase (AMPK) activator and showed its antiobesity effect. In this study, we investigated whether nectandrin B affects phosphorylation of endothelial nitric-oxide synthase (eNOS) in human endothelial cells. Nectandrin B increased the phosphorylation of eNOS and nitric oxide (NO) production in a concentration-dependent manner and maximal effect was found at 10 g/ml. Necta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Because the expression of P-Ser 15 -p53, a substrate of AMPK, was increased in old HDFs, and NecB was shown to stimulate the AMPK-related pathways in differentiated C2C12 cells [2729], the expression and phosphorylation status of AMPK were examined in HDFs. After treatment with vehicle, an AMPK activator AICAR (positive control), an AMPK inhibitor compound C (negative control), or 10−20 μg/mL NecB for 2 days, the protein levels in cell lysates were examined by western blot analysis for AMPK phosphorylation on Thr 172 (P-Thr 172 -AMPK; an activated form of AMPK) and total AMPK, using glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as an internal control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the expression of P-Ser 15 -p53, a substrate of AMPK, was increased in old HDFs, and NecB was shown to stimulate the AMPK-related pathways in differentiated C2C12 cells [2729], the expression and phosphorylation status of AMPK were examined in HDFs. After treatment with vehicle, an AMPK activator AICAR (positive control), an AMPK inhibitor compound C (negative control), or 10−20 μg/mL NecB for 2 days, the protein levels in cell lysates were examined by western blot analysis for AMPK phosphorylation on Thr 172 (P-Thr 172 -AMPK; an activated form of AMPK) and total AMPK, using glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as an internal control.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, NecB was suggested as an AMPK activator in various cell types, including human HDFs [27], hepatocytes [33], rat VSMCs [29], and differentiated C2C12 cells [28]. It was also shown that the activation capacity of AMPK declines during aging [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DAF-2 DA interacts with NO and NO-derived nitrosating species to produce a fluorescent by-product [19], which can be used as an indicator of NO synthesis in living cells [20]. This method has been used successfully in endothelial cells [21] and has been adapted herein for use in C2C12 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic factors cannot enter the lower layer of intestinal mucosa. As a commonly used drug, SSP is composed of many active components, such as evodiamine, schizandrin A, myrislignan, and macelignan, which have a wide range of pharmacological effects, including anti-inflammation, antitumor, anti-free radicals, and regulating immunity [38][39][40]. Numerous studies have shown that myrislignan protects skin keratinocytes from ultraviolet B-induced damage and reduces the activation of MAPK and PI3K/Akt [41].…”
Section: Discussionmentioning
confidence: 99%